E LEARNING AND NEURAL NETWORKS - Usman Arif (International Journal of Contemporary Issues in Social Sciences, 2024)
The digital technology is affecting educational media including Multimedia , Learning Management Systems and Hypermedia. Neural Networks and e-learning provides the student and teachers an opportunity to interact with many applications such as video conferencing , lectures on Microsoft teams which supports audio , chat and e white boards. The e universities are now adapting the learning styles of students by linking environment technology in neural networks such as CHAT GPT. The digital data is coded through machine language into graphical design , shapes , facts and figures and presented into human form through artificial neural networks. The 5G network ecosystems presents new technologies of optronics and visual aids in neural networks in teaching. The neural networks learn from human experiences through neuro optical logic and handles large amount of data set. Neural networks make faster decisions in e learning as personalized changes in learning by students to produce results after processing the inputs. The optronics is a new use of data communication by super intelligent machines for 4D imaging in field of tele communication , satellite imagery and mobile phones . The motion optronics will move the world at large from artificial intelligence towards super intelligence by running the new gadgets with supertonics running on smart chips .